Fostering sustained learning among undergraduate students : emerging research and opportunities - Chemosit, Caroline (A volume in the Advances in higher education and professional development (AHEPD) book series, 2017)
"This book provides a step by step approach and implications to institutional policy and practices and faculty role in enhancing sustained learning. Further, opportunities and challenges relative to sustained learning are highlighted with a view of maximizing the prospects. The students' perspectives provided give a better view of the interplay of factors that influence sustained learning"--